The Use of Realia to Improve Young Learners’ Vocabulary - Pritania Mokalu (Journal of English Language Teaching, Literature and Culture, 2022)
This study is to find out the effectiveness of using the realia in improving young learners vocabulary.  This study was a library research. Realia is a real-life object that can be used in the classroom in order to help the learning process. The result of this study show that The usage of realia in the classroom is regarded to be beneficial in the learning process. There are numerous benefits to doing so, including: the learning experience becomes more memorable for the student. Because the roles of the students are also crucial in supporting the lesson, the students were more active in receiving information during the learning process, the items were easily recognized and their names were quickly remembered by the students. Last but not least their interest in the lesson was piqued, and they were less likely to become bored during the lesson.